2021
DOI: 10.1177/09670335211054303
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared spectroscopic and aquaphotomic evaluation of the efficiency of solar dehydration processes in pineapple slices

Abstract: Parallel transformation tests on pineapple slices using two micro drying plants (M1 and M2) operating with solar energy were carried out. Method M1 consisted of an active fan at the top, whose ventilation rate depended on the internal temperature. Method M2 had a continuously working fan at the bottom. The dehydration performance of these two micro-plants was compared by collecting spectra from pineapple slices in reflectance mode (900–1600 nm) at three different times: (0) process start, (1) during the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…They are especially significant in the range 1409–1453 nm. The water absorption at 1441 and 1447 nm is important in desiccation processes and abiotic stress [ 35 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are especially significant in the range 1409–1453 nm. The water absorption at 1441 and 1447 nm is important in desiccation processes and abiotic stress [ 35 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aquaphotomics analysis of water–light interactions is a new source of information for a better understanding of the biological world. The combination of NIRS and aquaphotomics has already been used for the non-destructive investigation of aqueous and biological systems, for the evaluation of fresh and processed fruits and vegetables quality [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ], plant abiotic stress and diseases [ 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Manyako et al [44], in their research, considered the possibility of using energy from solar panels to obtain a large amount of saturated steam, which is used in the production of essential oils from fruits. Cattaneo et al [45] examined the possibility of using a solar power plant in fruit drying processes to increase dehydration. Based on these and similar studies, it can be confirmed that the use of solar power plants contributes to the efficiency of food companies' business operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research aimed to utilize aquaphotomic NIRS for monitoring during cold storage and better understanding of the mechanisms for maintaining freshness, choosing the strawberry fruit as a fruit-model system. The combination of NIRS and aquaphotomics has been already used to monitor aqueous and biological systems non-invasively for various purposes, such as evaluation of fresh and processed fruits and vegetables quality (36)(37)(38)(39)(40)(41)(42), milk quality (43,44), viral infections in plants, bacterial cultures (45,46) and fermentation (47)(48)(49), and physiological monitoring and diagnostics in higher organisms (50)(51)(52)(53)(54)(55). The second aim of the investigation was to compare the effects of different cooling technologies on the preservation of strawberries.…”
Section: Introductionmentioning
confidence: 99%